2018
DOI: 10.1038/s41598-018-25796-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth of ‘W’ doped molybdenum disulfide on graphene transferred molybdenum substrate

Abstract: In the present study, a novel method has been carried out to grow tungsten (W) doped molybdenum disulfide (MoS2) on the graphene transferred TEM grid in a chemical vapor deposition (CVD) setup. Tungsten trioxide (WO3) has been used as a source for ‘W’ while ‘Mo’ has been derived from Mo based substrate. Different experimental parameters were used in this experiment. Higher gas flow rate decreases the size of the sample flake and on other side increases the dopant concentrations. The interaction mechanism betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Beyond those conventional non-isoelectronic doping, isoelectronic substitution doping is also achieved in 2D materials, such as Se-doped MoS 2 [176] and W-doped MoS 2 . [177] A large portion of substitutional doping for 2D materials is performed during the in situ growth. [178][179][180] For example, Li et al [178] demonstrated p-type large-area monolayer Nb-doped MoS 2 by a one-step salt-assisted CVD process.…”
Section: Substitutional Doping and Alloyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond those conventional non-isoelectronic doping, isoelectronic substitution doping is also achieved in 2D materials, such as Se-doped MoS 2 [176] and W-doped MoS 2 . [177] A large portion of substitutional doping for 2D materials is performed during the in situ growth. [178][179][180] For example, Li et al [178] demonstrated p-type large-area monolayer Nb-doped MoS 2 by a one-step salt-assisted CVD process.…”
Section: Substitutional Doping and Alloyingmentioning
confidence: 99%
“…Beyond those conventional non‐isoelectronic doping, isoelectronic substitution doping is also achieved in 2D materials, such as Se‐doped MoS 2 [ 176 ] and W‐doped MoS 2 . [ 177 ]…”
Section: Strategies Of P‐type Engineering In 2d Semiconductors For We...mentioning
confidence: 99%
“…Two-dimensional (2D) transition metal dichalcogenides (TMDs) materials are attracting a significant deal of interest due to their unique properties and great potential for applications in nanotechnology [1,2,3]. Among all 2D TMDs, Molybdenum disulfide (MoS 2 ) has turned out to be one of the most interesting materials for applications due to a series of special and tunable physical and chemical properties [4,5,6] in various fields with potential as field-effect transistors [7], solar energy devices [8], energy conversion [9] and energy storage devices [10], photoluminescence [11], catalysis for hydrogen evolution reaction [12], piezoelectric devices [13], photo-electro catalysis [14,15] electrical-thermal conductivity [16,17] and sensor technologies [18,19].…”
mentioning
confidence: 99%